Role and perspective of Azotobacter in crops production - Reginawanti Hindersah; Nadia Nuraniya Kamaluddin; Suman Samanta; Saon Banerjee; Sarita Sarkar (Universitas Sebelas Maret, 2020)
Low nitrogen content in soil is usually overcome by chemical fertilization. After long application period, high-dose and intensive use of N fertilizers can cause ammonia volatilization and nitrates accumulation in soil. In sustainable agriculture, the use of bacterial inoculant integrated with nutrient management system has a role in soil health and productivity. Azotobacter-based biofertilizer is suggested as a chemical nitrogen fertilizer substitute or addition in crop production to improve available nutrients in the soil, provide some metabolites during plant growth, and minimize fertilizer doses. The objective of this literature reviewed paper is to discuss the role of Azotobacter in agriculture; and the prospective of Azotobacter to increase yield and substitute the chemical fertilizer in food crops production. The results revealed that mechanisms by Azotobacter in plant growth enhancement are as biofertilizer, biostimulant, and bioprotectant. Nitrogen fixation by Azotobacter is the mechanism to provide available nitrogen for uptake by roots. Azotobacter stimulates plant growth through phytohormones synthesis; indole acetic acid, cytokinins, and gibberellins are detected in the liquid culture of Azotobacter. An indirect effect of Azotobacter is exopolysaccharide production and plant protection. Inoculation of Azotobacter in the field integrated with organic matter and reduced chemical fertilizer are reported to improve plant growth and yield.